Misja na wschodzie. Wizyty kard. Józefa Glempa w ZSRS w 1988 roku oraz ich polityczno-międzynarodowy kontekst - Kowal, Paweł (Dzieje Najnowsze, 2016)
Mission in the East. Visits to the Soviet Union Paid by Cardinal Józef Glemp in 1988 and Their Political–international Context Two visits paid to the Soviet Union by the Primate of Poland, Cardinal Józef Glemp, in 1988 were an unprecedented event within the context of the state–Church relations prevalent in the USSR. This article not only deals with their details but also shows them within a wide context of the political objectives of the Apostolic See steered by John Paul II, the policies of the General Wojciech Jaruzelski team in Poland, and the political plans of Mikhail Gorbachev within his perestroika programme, thus enhancing the diplomatic–pastoral significance of both journeys made by the Primate of Poland. The author proposed hypotheses explaining the reason why the significance of the visits paid by Cardinal Glemp, the first as part of an official delegation of the Apostolic See attending celebrations of the Millennium of the Christianization of Russia, was limited. At the same time, the article demonstrates the great rank of the Cardinal’s activity from the viewpoint of a revitalisation of Church administration in the member–countries of the former USSR and a revival of the socio–cultural life of Poles living in the East.